Estudio ambiental para el desarrollo de la actividad minera artesanal no metálica, en la concesión minera El Castillo de Jepelacio - Díaz Loja, Yesica Magaly (2016)
Nonmetallic mining, as the great majority of human activities, is being exploited by informal without any permission, generating impacts to the environment, damage to biodiversity causing loss and migration of native species, and other environmental problems that might exist. lt is for it that the present qualified study of investigation " ENVIRONMENTAL STUDY FOR THE DEVELOPMENT OF THE MINING HANDCRAFTED NOT METALLIC ACTIVITY, IN THE MINING CONCESSION JEPELACIO CASTLE, 2014" located in Jepelacio District. According to the regulations in force. For the realization of the project was initially done the screening process taking as a basis the general data of the project, to then make a brief description of the project and the environmental characteristics of the environment, identifying the significant environmental impacts, using the qualification criteria for environmental components affected, and thus to take proposals of mitigation measures according to the category 1 to that belongs to the project. lt presents the description of the different stages that comprises the project as are construction, operation, maintenance and close post closure, subsequently makes a description of the environment taking as a reference the variables physiography, geology, soil, natural hazards, climate, hydrology. Through bacteriological examination it was determinad that the water body that crosses the concession is not suitable for human consumption by presenting fecal coliforms and through the analysis physical, chemical parameters were evaluated of turbidity, pH, conductivity, SST, total hardness. lt carried out the identification and evaluation of environmental impacts using the Leopold array where were related components with the stages of the project, valuing the impacts according to the table scale. Proposed measures for the prevention, control and mitigation, environmental monitoring plan, contingency plan, community plan of relations and conceptual closure plan. Finally in annexes are observed the maps showing the location of the project, quantitative anatysis and bacteriological water and photos of the non-metallic mining concession. Key words: nonmetallic mining, environmental impacts.